A study to compare efficacy of non cultured autologus melanocyte transfer versus punch grafting technique for stable vitiligo patients - Ambresh S Badad; Amrit Singh Bhatia; Ashok Hogade; Shruti Ambresh Badad; Debdeep Mitra (Wolters Kluwer Medknow Publications, 2022)
Background: Vitiligo is a common acquired idiopathic hypomelanosis, which is characterized by loss of melanocytes in the epidermis associated with autoimmune and hereditary causes. The various surgical modalities available are tissue grafting techniques such as punch grafts, suction blister grafts, and split-thickness grafts as well as cellular grafts such as autologous noncultured epidermal cell suspensions and cultured melanocyte suspensions. Objective: We aimed to study and compare the efficacy of noncultured melanocyte transfer technique and punch grafting technique in the management of stable vitiligo. Materials and Methods: Fifty patients of both sexes between the ages of 15 and 50 years having stable vitiligo for minimum 1 year were included in the study and divided in two groups. Group 1 was treated with autologous noncultured melanocyte-rich cell suspension and Group 2 was treated by punch grafting technique. Response to treatment was evaluated on the basis of degree of repigmentation (both subjective and objective assessment), which was carried out at monthly intervals for a period of 6 months along with clinical photographs. Results: The results were statistically analyzed using "Chi-square test" and "statistical significance" (p-value) methods. An excellent (>75% repigmentation) result was obtained in 77.27% of patients by NCMT (noncultured melanocyte transfer) technique whereas good (60%-75% repigmentation) result was obtained in 78.57% of patients by punch grafting technique after 6 months. Conclusion: Noncultured melanocyte transfer is a simple and effective technique to produce uniform pigmentation in short duration and is suitable to cover large body surface areas with a cosmetically better outcome and is better than punch grafting.